2013
DOI: 10.4238/2013.october.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Cellular responses induced in vitro by pestheic acid, a fungal metabolite, in a gastric adenocarcinoma cell line (PG100)

Abstract: ABSTRACT. There is a constant search for new cancer treatments that are less aggressive and economically affordable. In this context, natural products extracted from plants, fungi, and microorganisms are of great interest. Pestheic acid, or dihidromaldoxin, is a chlorinated diphenylic ether extracted from the phytopathogenic fungus Pestalotiopsis guepinii (Amphisphaeriaceae). We assessed the cytotoxic, cytostatic, and genotoxic effects of pestheic acid in a gastric adenocarcinoma cell line (PG100). A decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Thus, the authors summarized that the possible mechanism, pestheic acid ( 16 ), could enhance recombination or induce chromosomal aberrations by interfering with chromatin structure and/or the proteins. Moreover, they also proposed another possible mechanism to explain the genotoxic effects of polybrominated analogs that could create reactive oxygen species (ROS) to induce DNA damage …”
Section: Bioactivities Of Asterric Acid Analogsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the authors summarized that the possible mechanism, pestheic acid ( 16 ), could enhance recombination or induce chromosomal aberrations by interfering with chromatin structure and/or the proteins. Moreover, they also proposed another possible mechanism to explain the genotoxic effects of polybrominated analogs that could create reactive oxygen species (ROS) to induce DNA damage …”
Section: Bioactivities Of Asterric Acid Analogsmentioning
confidence: 99%
“…16 In 2013, Bahia et al assessed the cytotoxic, cytostatic, and genotoxic effects of pestheic acid (16) in a gastric adenocarcinoma cell line (PG100), and observed a decrease in clonogenic survival and significant increases in both micronucleus and nucleoplasmic bridge frequency but no changes in cell cycle kinetics or apoptosis induction. 71 Thus, the authors summarized that the possible mechanism, pestheic acid (16), could enhance recombination or induce chromosomal aberrations by interfering with chromatin structure and/ or the proteins. Moreover, they also proposed another possible mechanism to explain the genotoxic effects of polybrominated analogs that could create reactive oxygen species (ROS) to induce DNA damage.…”
Section: Cytotoxic Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack in PG100 cell line of the TP53 gene, which is common in gastric cancers, could determine the absence of repair checkpoints. Pestheic acid ( 29 ) showed clear cytotoxic effect but only at high concentration with a IC 50 of 50.5 μg/mL, which demonstrated that it is not a potent anticancer compound [ 45 ].
Fig.
…”
Section: Metabolites From Endophytic Fungimentioning
confidence: 99%
“…P. guepinii metabolites of ciprofloxacin and norfloxacin [96] culture broth extract inhibit actinomycete growth [97] pestheic acid or dihidromaldoxin genotoxicity and mutagenicity [98] alpha-pyrones [99] P. hainanensis taxol [19] caryophyllene-Type Sesquiterpenes [100] P. heterocorni 7-hydroxy-5-methoxy-4,6-dimethyl-7-O-α-L-rhamnosyl-phthalide and 7-hydroxy-5-methoxy-4,6-dimethyl-7-O-β-D-glucopyranosyl-phthalide [101] heterocornols A-L, methyl-(2-formyl-3-hydroxyphenyl) propanoate, cladoacetal A, xylarinol A, agropyrenol, vaccinol G, (R)-3-hydroxy-1-[(R)-4-hydroxy-1,3-dihydroisobenzofuran-1-yl]butan-2-one, and (R)-3-hydroxy-1-[(S)-4-hydroxy-1,3-dihydroisobenzo -furan-1-yl]butan-2-one cytotoxicity and antifungal [29] pestaloisocoumarins A and B, isopolisin B, pestalotiol A, gamahorin, pestalachloride B, pestalachloride E, pestalalactone atropisomers (8a/8b), cytotoxicity [30] heterocornols M and N, heterocornols O and P anticancer [28] P. humus pestynol antibacterial and antifungal activity, weak cytotoxicity [102] pestiocandin antibacterial and antifungal activity [103] P. jesteri jesterone and hydroxy-jesterone selective antimycotic activity [104] P. karstenii pestalrone A, pestalrone B, pestalotin, hydroxypestalotin cytotoxic activity, antiprotozoal activity [42] P. leucothës BS, GS, and YS Immunomodulatory [105] immunomodulatory effects [106] P. mangiferae 4-(2,4,7-trioxa-bicyclo [4.1.0] heptane-3-yl) phenol antibacterial and antifungal activity [107] P. microspora taxol antiproliferative activity [11,108] α-pyrone [109] (+)-dendocarbin L, (+)-sydonic acid, and (+)-sydowic acid cytotoxicity [68] isopestacin antifungal and antioxidant activities [110] pestalotiollide B [49,[111][112][113] pestalotiollide B, melanin [114] 7-epi-10-deacetyltaxol induces apoptosis [115] taxol, pestalotiollide B, 1, 8-dihydroxy naphthalene melanin antitumor [13] melanin [116]…”
Section: Fungal Species Metabolites Bioactivity Referencesmentioning
confidence: 99%